2021
DOI: 10.3390/ijms22031121
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Kidney Graft Viability and Its Cells Metabolism during Machine Perfusion

Abstract: Kidney transplantation is the golden treatment for end-stage renal disease. Static cold storage is currently considered the standard method of preservation, but dynamic techniques, such as machine perfusion (MP), have been shown to improve graft function, especially in kidneys donated by extended criteria donors and donation after circulatory death. With poor organ quality being a major reason for kidneys not being transplanted, an accurate, objective and reliable quality assessment during preservation could a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 84 publications
0
12
0
2
Order By: Relevance
“…Our data also indicate that, at the immediate post-transplantation period, ischemia-reperfusion injury may increase the antigenicity of the kidney graft. Hence, efforts to alleviate kidney transplant ischemia-reperfusion injury by evolving and applying more efficient preservation methods may be proven beneficial [52]. Finally, our study showed that ischemiareperfusion increases RPTECs' antigenicity by enhancing ICAM-1 expression.…”
Section: Discussionmentioning
confidence: 59%
“…Our data also indicate that, at the immediate post-transplantation period, ischemia-reperfusion injury may increase the antigenicity of the kidney graft. Hence, efforts to alleviate kidney transplant ischemia-reperfusion injury by evolving and applying more efficient preservation methods may be proven beneficial [52]. Finally, our study showed that ischemiareperfusion increases RPTECs' antigenicity by enhancing ICAM-1 expression.…”
Section: Discussionmentioning
confidence: 59%
“…In hypothermic conditions, options to assess kidney function are limited. Indeed, the metabolic rate at 4°C is limited to 10% of that at physiological temperature with a 40% lower rate of chemical reactions ( 24 ). Furthermore, in the majority of cases there is no active oxygenation during hypothermic kidney perfusion in which case aerobic metabolism is not supported ( 25 ).…”
Section: Kidneymentioning
confidence: 99%
“…Cell metabolism correlates closely with perfusion; therefore, in IRI, metabolism becomes deranged and can lead to alterations in the electron transport chain as well as increased levels of ROS. When damage remains below a certain threshold, the renal tubules are able to repair the damage, mitigating the loss of functioning parenchyma and glomerular filtration ability [ 100 ]. Therefore, as essential as reperfusion is for cell survival, it is this same reperfusion that can also accelerate the apoptotic pathways in IRI.…”
Section: Literature Searchmentioning
confidence: 99%